Discussion paper: effect of the nanosolution concentration on a heated surface of the heat transfer enhancement using twin impingement jet mechanism - Faris Abdullah, Mahir; Zulkifli, Rozli; Zulkifli, Rozli; Harun, Zambri; Abdullah, Shahrir; Aizon W Ghopa, Wan (International Journal of Engineering and Technology, 2019)
The range of industrial applications with impinging jets is wide for cooling and heating engineering and industrial applications due to its high convective heat transfer coefficients. This study noted the lack in the information of using Nano surface coated aluminium plate on the heat transfer enhancement. There is a clear gap about using Nanosolution coating in the twin impingement jet technique. Furthermore, the interaction between the correlated factors and the correlation relates Nusselt number with the significant parameters have not been investigated before. The main objective of this article is to present the methodology associated with mixing region of twin jets arrangement for flow and heat transfer enhancement. This research will present a study which sought to enhance heat transfer by employing a twin jet impingement mechanism, impact of using Nanocoating on the surface plate and investigating the impact of the distance between the nozzles and plate, Reynolds number and the spacing between nozzles at the horizontal distance from stagnation point on the Nusselt number (Nu). The design of experiments approach (DOE) that employed response surface methodology (RSM) will use to conduct the heat transfer parametric study. This research will use 3 different heat transfer enhancement processes, considered the TiO2 nanosolution coat, aluminium plate heat sink and a twin jet impingement system. The researchers could prepare different nanosolution, which consisted of varying nanoparticle concentrations, and coated them on the metal surface. Thereafter, researchers have to carried out (XRD) and (FESEM) analysis for determining the structure and the homogeneous surface coating of the nanosolution. the results of this study will design the methodology of this research. This technique will achieve the mission to improve the performance of various industrial and engineering applications.Â Â